Keberhasilan Penggunaan Media dan Model Pembelajaran Make A Match Dalam Meningkatkan Minat Peserta Didik Terhadap Pembelajaran Bahasa Inggris di SDN Angkasa - ana khoerunisa; erwin rahayu saputra (Papanda, 2024)
In the Indonesian education curriculum, English is one of the subjects that must be studied, seen from the fact that English itself is an international language and with the development of globalization, English has become one of the skills that students must possess must, therefore English needs to be taught to students. students, where learning English can improve students' communication skills, and can expand students' educational and career opportunities. However, in practice, students' interest in learning English is at a low level, this is because the lessons are difficult, so it is difficult to understand them, and students become lazy and lack enthusiasm in participating in English language learning. So this article was created to look at the use of learning models and media in increasing the interest of class 3A students at SDN Angkasa towards learning English with the material Names room at school. This research was carried out using narrative inquiry and qualitative methods. The use of learning models and learning media has a big influence in increasing students' interest in learning English, the use of learning media in the form of pictures or Flash Cards containing rooms in the school can attract students' attention so that they want to take part in learning, use The make a machine model also supports creating a fun learning atmosphere, where this model contains game elements so that it can increase students' interest in participating in learning, this can be seen from the enthusiasm of students when they participate in learning activities with enthusiasm, and students are able to understand the material. delivered so that students can do the practice questions correctly Keywords: English Language, Media, Model